Reflections on the large-scale application of a community resilience measurement framework across the globe - Adriana Keating; Stefan Hochrainer-Stigler; Reinhard Mechler; Finn Laurien; Naomi Rubenstein; Teresa Deubelli; Stefan Velev; Michael Szoenyi; David Nash (Climate Services)
This paper reflects on learnings and analysis from an extensively globally applied, standardized community disaster resilience measurement framework that utilises bottom-up (locally collected) data. These lessons, from over a decade of on-the-ground work and analysis, are based on empirical evidence and have salience for scholars, policy-makers and practitioners aiming to strengthen community disaster resilience and apply bottom-up community disaster resilience measurement approaches. The Flood Resilience Measurement for Communities approach was co-designed and implemented by the Zurich Flood Resilience Alliance: a transdisciplinary science-policy-practice collaboration including scientists, practitioners and private business. It has been applied globally in approximately 400 communities worldwide, demonstrating the real-world impact of scalable community disaster resilience measurement initiatives. Findings provide evidence for the impacts and good practices of applying bottom-up community disaster resilience measurement approaches. Quantitative analysis on this unique dataset provides new entry points for research on typologies and dynamics of resilience, based on empirical evidence on human, social, physical, natural and financial dimensions. Based on our analysis, we find that the use of bottom-up, multidimensional, standardized community disaster resilience measurement approaches is a worthwhile endeavour to support community disaster resilience strengthening.